SISTEM INFORMASI PENYEDIA LAYANAN PERANGKAT LUNAK GRATIS UNTUK IDEVICE BERBASIS WEB - Widianto, Wahyu; Hamzah, Amir; Iswahyudi, Catur (Jurnal Script, 2014)
ABSTRACTiOS operating system (i Operation system) Apple is growing rapidly and rise in popularity since it was first released. Moreover, the software that supports it, by building an information system software providers. This system is an information system that provides information software to allow the iDeviceÂ  users in searching free software. On information systems software service providers are free to iDevice option menus. These menus are fitur system option for visitors to use in selecting and sorting software that visitors are looking for, such as category, menu search and tag (label) that distinguishes software supporting the device. The information system service provider develoved with PHP and CMS systems that is content management system. This study successfully implemented CMS method with the end result in the form of information systems service providers free software for web-based iDevice. With several advantages, namely a simple web interface, which allows visitors to view a search software, information systems service providers free software for web-based iDevice serves as a search tool for software iDevice users of the iPhone, iPod and iPad.Â Key Words: Apple, Information system, iDevice, Software.